SP1.1.2 The significant impact of using virtual cross match on achieving 100% within-18 hour target of cold ischaemia time in transplanting kidneys from donors following brain death in a single centre in UK. (9th August 2022) - Tasleem, Sadia; Austin, Sharlene; Lennon, Veronica; Mckane, William; Pararajasingham, Ravi; Marie, Yazin
Abstract: Aims: To evaluate the impact of virtual cross match in donation following brain death (DBD) kidney transplants on the cold ischaemia time (CIT) as one of the factors in achieving better renal graft outcomes. Methods: Every patient on the deceased donor renal transplant waiting list in our centre was asked to give a blood sample to test for Human Leucocyte Antigen (HLA) antibodies. Our transplant coordinators ensured that this process is updated three monthly as part of the eligibility criteria to perform virtual cross match. Other factors contributing to CIT were intentionally ignored given that there are no significant changes in the kidney allocation scheme or kidney acceptance criteria. Comparison was made between CIT in the financial years 2014/ 2015 and 2020 /2021. Results: Since the introduction of this strategy, our centre was the only centre in all 23 UK kidney transplant centres to achieve 100% transplantation within 18 hour CIT for DBD kidneys transplants in the financial year 2020/2021. This represented a significant improvement compared to 58% in the financial year 2014/2015. Conclusions: Virtual cross match was a key factor in achieving the 18 hours target for DBD kidney transplant regardless of other contributing factors. It is highly recommended that a three-monthly screening for HLA Antibodies is regularly performed to achieve this result.